Pengaruh Perilaku Guru dan Pembelajaran Daring terhadap Prestasi Belajar Akidah Akhlaq - Emy Sa’adah Mahsunah; Maragustam Siregar (Fahima, 2022)
The pandemic condition causes the learning process to be diverted into an online system. The teacher's behavior changes in an effort to make adjustments along with the changes in learning. Therefore, the authors are interested in researching teacher behavior and online learning. This study aims to conduct research on the effect of teacher behavior and online learning on Akidah Akhlaq learning achievement in students of SMP Al-Muayyad Surakarta in the academic year 2020/2021. This research method is a type of quantitative research with the independent variable (X) is teacher behavior and online learning and the dependent variable (Y) is Akidah Akhlaq learning achievement. The population in this study amounted to 134 and a sample of 47% or 64 students. The results of the questionnaire were analyzed by T-test and F-test, termination coefficient (R-square) and multiple linear regression analysis with the results that all independent variables (X) simultaneously had a positive and significant effect on the dependent variable (Y).